Mnemotechnics and Ludic Strategies in Teaching Polish as a Native and Foreign Language - Kuźma, Natalia (Ludicity in (Glotto)Didactic, 2020)
Ludic techniques are more and more widely increasingly used in language teaching. In relation to the Polish language, there are no studies focusing on the mnemotechnical use of games and plays. The aim of this article is to present selected games and activities in the context of the role of mnemotechnics in the process of teaching Polish as a foreign language and as a native language. The paper presents the function of mnemotechnics, and a general outline of games and plays. The author presented three different games and the ways of playing them. “Dixit” and “Taboo” games were reviewed, as well as methods of using them them in Polish language lessons in a primary school at all levels of education and high school. In addition, she described examples of using these games in teaching Polish as a foreign language.